The AKT Pathway and Satellite Cell Activation in Skeletal Muscle Mass Regulation - Sofiyanti, Santi; Goenawan, Hanna; Lesmana, Ronny; Tarawan, Vita Murniati (Folia Medica Indonesiana, 2022)
Highlight: • AKT or protein kinase B increase protein synthesis and control the degradation of proteins. • Satellite cells was provided remarkable ability to regenerate skeletal muscle. • Stimulation of protein synthesis is effective therapy to maintain muscle mass, prevent muscle wasting to reduce risk sarcopenia and improve quality of life in the elderly. Abstract: Muscles have an important role as a regulator of glucose and triglyceride metabolism. Some researches show the correlation between skeletal muscle mass and metabolic diseases, such as diabetes. Skeletal muscle mass decrease occurs due to chronic illness or physiological process of aging, thus increasing the risk of metabolic diseases as well as motion difficulty in the elderly. Skeletal muscle mass depends on balanced protein synthesis and degradation, controlled through a variety of signal transduction pathways including the AKT. AKT or protein kinase B increases protein synthesis through the mTOR and GSK3β and controls the degradation of proteins through FoxO transcription factors. Another factor that has an alleged role in the regulation of skeletal muscle is the satellite cells which provide remarkable ability to regenerate skeletal muscle. A comprehensive understanding of the biomolecular mechanism of muscle mass regulation is important to develop effective treatment or prevention of muscle atrophy in many cases, either caused by pathological conditions, such as chronic diseases, or the process of aging.